Strategic Policy for Acceleration and Optimization of Border Area Development - Endang Try Setyasih; Bambang Heru Purwanto; Eddy Jusuf Sp (Doctoral Program of Social Science Pasundan University, 2020)
Most of the regions in the border are less developed due to the development paradigm in the past, more emphasizing the security approach rather than the security approach and inward-looking instead of outward-looking. In essence, the government has been striving to expedite border region development, but the border region is still less developed and marginalized. The roadmap of authority in border areas yet to be delimited between Government and Local Government, lack of synergic coordination, limited budget, the hardship of topographical features, isolated, remote, and inaccessible areas are the major problems. Therefore, to rapidly foster and prosper millions living in border regions, the government should formulate strategic and stringent policies.